Eksplorasi Pengalaman Belajar Siswa Kelas 10 TITL Dalam Pembelajaran PAI Melalui Vidio Animasi Interaktif di SMK Angkasa Mojokerto - Imam Wahyudi; Badiatus Sa’adah (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2026)
This study addresses the issue of low motivation and understanding of 10th-grade Electrical Power Installation Engineering (TITL) students at SMK Angkasa Mojokerto regarding Islamic Religious Education (PAI), caused by unappealing conventional learning methods. The purpose of this study was to explore students' learning experiences through the use of interactive animated videos in PAI learning and to identify their perceptions, engagement, and impact on student motivation and understanding. The method used was a descriptive qualitative case study approach, involving one PAI teacher and two 10th-grade TITL students as informants through structured in-depth interviews. The results showed that interactive animated videos were able to increase student engagement and motivation, particularly through interactive features such as quizzes, and facilitate understanding of conceptual PAI material through systematic visualization. However, student responses varied according to individual learning styles, with videos being more effective as a learning aid rather than a substitute for the teacher. In conclusion, the use of interactive animated videos is effective as a PAI learning medium when combined with direct teaching methods, thus a hybrid approach is highly recommended